The difference in waste generation reporting compliance of districts/cities before and after the issuance of the Ministry of Environment and Forestry Regulation Number 6 of 2022 - Purba, Seri Ulina (TROPHICO, 2025)
Waste management in Indonesia faces significant challenges, especially in providing accurate and up-to-date waste generation data at the district/city level. The National Waste Management Information System (SIPSN), managed by the Ministry of Environment and Forestry (KLHK), serves as the main reporting platform. However, compliance with waste generation reporting was low and inconsistent before the issuance of Ministerial Regulation No. 6 of 2022. This study aims to analyze the differences in compliance levels of waste generation reporting by districts/cities before and after the enactment of Ministerial Regulation No. 6 of 2022. A quantitative comparative approach was used, involving all 511 districts/cities in Indonesia as the study population. Secondary data on waste reporting from SIPSN for the periods 2020–2021 (before regulation) and 2023–2024 (after regulation) were analyzed. Compliance was categorized into three groups and analyzed using Wilcoxon Signed Rank Test. Significant differences in compliance levels were found before and after the regulation (p = 0.0001). After regulation, the number of compliant districts/cities increased substantially, while non-reporting decreased markedly. Significant differences in compliance levels were found before and after the regulation (p = 0.0001). After regulation, the number of compliant districts/cities increased substantially, while non-reporting decreased markedly.